Epidemiology, molecular characterisation and antimicrobial susceptibility of Neisseria gonorrhoeae isolates in Madrid, Spain, in 2016. (2019) - Guerrero-Torres, M. D.; Menéndez, M. B.; Guerras, C. S.; Tello, E.; Ballesteros, J.; Clavo, P.; Puerta, T.; Vera, M.; Ayerdi, O.; Carrio, J. C.; Mozo, I.; Del Romero, J.; et al.
Abstract: With the aim to elucidate gonococcal antimicrobial resistance (AMR)–risk factors, we undertook a retrospective analysis of the molecular epidemiology and AMR of 104 Neisseria gonorrhoeae isolates from clinical samples (urethra, rectum, pharynx and cervix) of 94 individuals attending a sexually transmitted infection clinic in Madrid (Spain) from July to October 2016, and explored potential links with socio-demographic, behavioural and clinical factors of patients. Antimicrobial susceptibility was determined by E -tests, and isolates were characterised by N. gonorrhoeae multi-antigen sequence typing. Penicillin resistance was recorded for 15.4% of isolates, and most were susceptible to tetracycline, cefixime and azithromycin; a high incidence of ciprofloxacin resistance ( 40%) was found. Isolates were grouped into 51 different sequence types (STs) and 10 genogroups (G), with G2400, ST5441, ST2318, ST12547 and G2992 being the most prevalent. A significant association ( P = 0.015) was evident between HIV-positive MSM individuals and having a ciprofloxacin-resistant strain. Likewise, a strong association ( P = 0.047) was found between patient age of MSM and carriage of isolates expressing decreased susceptibility to azithromycin. A decrease in the incidence of AMR gonococcal strains and a change in the strain populations previously reported from other parts of Spain were observed. Of note, the prevalent multi-drug resistant genogroup G1407 was represented by only three strains in our study, while the pan-susceptible clones such as ST5441, and ST2318, associated with extragenital body sites were the most prevalent.